Transition in the forest sector of the Republic of Karelia, Russia - Piipponen, Minna (Geographical Society of Finland, 1999)
This study examines the institutional setting of the forest sector in the Republic of Karelia, Northwestern Russia. Institutional settings are understood to include formal laws and regulations, as well as informal rules and social constraints that regulate the interaction of the actors in the regional forest sector. This study scrutinizes the actors’ interactions in relation to the attributes of rules-in-use, community and the forest resources, and outcomes from the interactions according to the Institutional Analysis and Development framework. Within this framework actors’ positions in the restructuring process from the planned economy towards functioning in the market are evaluated. The study explicates that, even if the sectoral restructuring has been going on for years, enterprises and organizations still negotiate about the outcomes of their interactions in favor of options which do not require too expensive investments towards the restructuring of their business practices. In addition, restructuring and reorganization is not just an economic process related to business practices and transactions. It is also entangled with other social and spatial structures and practices. This is most clearly visible in the social responsibilities of the enterprises and in their close connections to local communities. As a result, the current development of the forest sector is divergent.